2016
DOI: 10.1161/strokeaha.116.013021
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Computed Tomographic Perfusion in Thrombolysis for Minor Stroke

Abstract: Background and Purpose-The use of thrombolysis in acute minor ischemic stroke (MIS) remains controversial. We sought to determine the safety and efficacy of intravenous tissue-type plasminogen activator (IV-tPA) in acute MIS patients with demonstrable penumbra on computed tomographic perfusion study. Methods-Consecutive MIS patients with National Institutes of Health Stroke Scale ≤3 were identified from a prospective single tertiary-center database over a 4.5-year period (2011)(2012)(2013)(2014)(2015). Cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…This low rate is even more remarkable when one considers that it does not include the many patients who were excluded from thrombolysis based on small or absent perfusion lesions, who would be expected to have very low rates of sICH. A similar very low rate of sICH has also been seen in larger mCT cohorts . Comparing our network with other telestroke programs, our rate of independence of 55% compares favorably to published studies, with rates ranging from 34% to 49%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This low rate is even more remarkable when one considers that it does not include the many patients who were excluded from thrombolysis based on small or absent perfusion lesions, who would be expected to have very low rates of sICH. A similar very low rate of sICH has also been seen in larger mCT cohorts . Comparing our network with other telestroke programs, our rate of independence of 55% compares favorably to published studies, with rates ranging from 34% to 49%.…”
Section: Discussionsupporting
confidence: 84%
“…A similar very low rate of sICH has also been seen in larger mCT cohorts. 7,17 Comparing our network with other telestroke programs, our rate of independence of 55% compares favorably to published studies, with rates ranging from 34% to 49%. Those studies reported similar baseline NIHSS (range from 10 to 12, versus 10 in our study).…”
Section: Discussionsupporting
confidence: 74%
“…We should note that we did not evaluate the clinical profile behind the NIHSS, and were not able to assess the impact of different clinical syndromes (mainly aphasia or hemiparesis) on the functional outcome at 3 months. Finally, although perfusion imaging has been shown to be of interest in the context of low NIHSS strokes and arterial occlusion [18], this modality was not available for enough number of patients in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold has been previously used to assess the functional outcome of minor or mild stroke patients [18,19]. …”
Section: Methodsmentioning
confidence: 99%
“…The early and frequent use of multi-model imaging is useful in identifying stroke mechanism and predicting patients likely to worsen following IS [35] or may benefit from thrombolysis. [36] A limitation of our study is that multi-model imaging was completed in approximately 50% of patients. Our work is similar to the report of Ali et al [26] In their series, older patients with higher NIHSS, larger stroke size on imaging and poor collaterals were more likely to show progression.…”
Section: Plos Onementioning
confidence: 99%